2006
DOI: 10.1111/j.1540-4560.2006.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Contact, Forgiveness, and Experience of “The Troubles” in Northern Ireland

Abstract: Two studies used random sample surveys to test the “contact hypothesis” on intergroup attitudes of Catholics and Protestants in Northern Ireland. In Study 1, archival data from two different surveys in 1989 (N = 310 Catholics, 422 Protestants) and 1991 (N = 319 Catholics, 478 Protestants) showed that contact was positively related to attitudes toward denominational mixing. Study 2 (N = 391 Catholics, 647 Protestants) explored predictors of intergroup forgiveness, and also showed that intergroup contact was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
260
3
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(283 citation statements)
references
References 43 publications
15
260
3
5
Order By: Relevance
“…In Pettigrew and Tropp's (2006) meta-analysis of 516 studies which employed such an approach, as many as 95% reported a negative relationship between intergroup contact and prejudice. Additionally, friendships which transcend group boundaries have also been found negatively to correlate with prejudice (Hewstone et al 2006;Van Dick et al 2004). In the course of my focus group research the respondents indicated that they had a fairly high level of contact with Latvians either at work or in a social setting, and that they had little or no problems interacting with Latvians:…”
Section: (Postgraduate Respondent)mentioning
confidence: 99%
“…In Pettigrew and Tropp's (2006) meta-analysis of 516 studies which employed such an approach, as many as 95% reported a negative relationship between intergroup contact and prejudice. Additionally, friendships which transcend group boundaries have also been found negatively to correlate with prejudice (Hewstone et al 2006;Van Dick et al 2004). In the course of my focus group research the respondents indicated that they had a fairly high level of contact with Latvians either at work or in a social setting, and that they had little or no problems interacting with Latvians:…”
Section: (Postgraduate Respondent)mentioning
confidence: 99%
“…When ethno-political insecurities and resentments still linger from recent histories of violence, it is possible that they can be strategically appropriated by leaders in contentious political discourse. Of course, evidence exists which suggests that mutually exclusive ethnic and political identities and attitudes are capable of flux when the conditions or contexts In which intergroup relations are shaped are altered (Sonnenschein et al 2010;McGlynn et al 2004;Pickering 2006;Hewstone et al 2006). That sectarian hostilities persist does not necessarily imply that innovative forms of interethnic cooperation, and intra-ethnic heterogeneity, cannot take form (Fearon and Laitin 1996).…”
Section: Grounded Theory Analysis Of Interviews and Newspaper Reportsmentioning
confidence: 99%
“…Given the severity of political violence in the country at the time this was written, an obvious example is Rydgren andSofi (2011) andRydgren et al's (2013) research on the impact of cooperation between distinct ethno-religious groups in Iraq. Other examples include post-conflict research from Northern Ireland on the impact of interethnic contact and trust on political attitudes (Hewstone et al 2006;Tam et al 2009) or the promise of integrated education in reducing ethnic or religious intolerance and mistrust (McGlynn et al 2004). While the findings of such research are no doubt important in both theoretical and policy terms, approximately 95 percent of children in Northern Ireland attend segregated schools (Smithey 2011:15).…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations